LEGAL TRANSFER AND MERGER UNDER DIRECTIVE 2001/23/EC - Tamošiūnaitė, Eglė (Teisė, 2016)
The article studies the notion of legal transfer and merge as types of business transfer under Directive 2001/23/EC. The author summarizes that definition of legal transfer is explained broadly in the jurisprudence of the Court of Justice of the European Union. Therefore, it embodies types of business transfer of any legal form and does not anyhow restrict the scope of application of Directive 2001/23/EC. The author states that in practice, legal transfer can be implicated by a transaction, administrative act or judicial decision and gives related examples from the jurisprudence of Court of Justice of the European Union.As regards a notion “merger” in the context of the Directive 2001/23/EC, the author indicates that this notion refers to the types of reorganization of a legal person under national law. Accordingly, the provision of a merge, as a separate type of a business transfer, in the Directive 2001/23/EC is excessive since, in author‘s opinion, the notion of legal transfer is sufficient to cover the situations of reorganization of a legal person.The article also discusses, that national law provisions, which restrict termination of employment relationship due to a business transfer, should be revised. The author expresses opinion that their current wording allows an inaccurate interpretation – that reorganization or a change of members, subordination or name of the company determined by such reorganization are separate conditions to apply restriction for employment termination and does not fall under the scope of restriction to terminate employment due to a business transfer.